Individual Counseling to Increase Self-Confidence in Slow Learners at Mabdaul Falah Islamic Junior High School, Pamekasan, East Java - Tina Indriyani; Heri Fadli Wahyudi (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Children's learning abilities are often associated with their intellectual abilities. Children with learning disabilities (slow learners) have limitations in understanding lessons, which often leads to low self-confidence. This study aims to determine the implementation and results of individual counseling services in increasing the self-confidence of slow learners at MTs Mabdaul Falah Pamekasan. This study uses a qualitative approach with a case study method. Data were obtained through interviews, observations, and documentation involving two slow learners as the main subjects, as well as teachers and school staff as additional data sources. Individual counseling services were conducted in four sessions, including the opening stage, problem identification, diagnosis, treatment, and evaluation. The results showed that individual counseling services were effective in boosting the self-confidence of slow learners. This was evident from changes in student behavior, such as the courage to express opinions, increased participation in class discussions, and active involvement in school activities. However, these changes required ongoing support from the school environment and family. This study contributed to the development of individual counseling theory and practice, particularly in supporting slow learners to overcome their academic and social challenges.